Screening of starch quality traits in cassava (Manihot esculenta Crantz) - Sánchez, T.; Salcedo, E.; Ceballos, H.; Dufour, D.L.; Mafla, G.; Morante, N; Calle, F.; Pérez Velásquez, Juan Carlos; Debouck, Daniel G.; Jaramillo, Gustavo; Moreno, I.X. (Wiley, 2009)
Cassava (Manihot esculenta Crantz) is one of the most important sources of starch in the tropics. There is limited and contradictory information regarding cassava starch characteristics. The International Center for Tropical Agriculture (CIAT) holds in trust FAO's cassava germplasm collection. Starches from 3272 landraces (including 12 wild relatives) and 772 improved clones were extracted and analyzed over a period of several years. In most cases only one starch sample per genotype was analyzed. Average cyanogenic potential was 327 ppm but considerably higher in the landraces (340 ppm) than in improved clones (267 ppm). Average total and reducing sugars were slightly higher in improved clones (4.06 and 1.56%, respectively) than in landraces (3.68 and 1.25%, respectively). Amylose content was similar in both types of germplasm with an average of 20.7%. Average pasting temperature was 65.3°C. Maximum viscosity was 777.5 mPa s, breakdown was 298.1 mPa s, consistency was 155.8 mPa s and setback was -144.5 mPa s. The large sample of starches analyzed provides very robust information regarding the actual characteristics of cassava starch.